INTERNALISASI NILAI-NILAI SPIRITUAL UNTUK PEMBENTUKAN KARAKTER SISWA SD ISLAM KURMA SALATIGA - Nafingatun; Muh Nursikin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine in depth the mechanisms and strategies for internalizing spiritual values at SD Islam Kurma Salatiga in shaping student integrity, with a primary focus on exploring a holistic strategy that bridges ritualistic practices into transformative behavior. Employing a qualitative method with a case study design, data were collected through in-depth interviews, participant observation, and documentary studies, which were then analyzed using the interactive model of Miles, Huberman, and Saldana through the lenses of Herbert Kelman’s internalization theory and Al-Attas’s concept of ta’dib. The results indicate that the internalization of spiritual values is carried out through three simultaneous stages: first, the institutionalization of values through an integrated curriculum (hablum minallah, minannas, minal ‘alam), habituation, and teacher exemplary behavior (uswah hasanah); second, the subjectification of values through the pedagogical technique of the "CCTV analogy" to build ihsan awareness, which successfully shifts student motivation from external compliance to internal control (metaphysical integrity); and third, externalization and consistency through the "Smart Book" instrument and the POMG (Parents and Teachers Association) forum to ensure character continuity within the family environment. The novelty of this research proves that the synergy between logical supervision (the CCTV metaphor) and spiritual supervision effectively forms an "internal control system" in elementary school students, confirming that a holistic strategy integrating the roles of schools and parents is capable of transforming ritual obedience into autonomous self-integrity as a tangible manifestation of the khairu ummah generation amidst the challenges of the digital era.